Granuloma faciale from dermatoscopic perspective - Jinal Jainendra Tandel; Pragya Ashok Nair (Wolters Kluwer Medknow Publications, 2023)
Granuloma faciale (GF) is a rare and benign skin disease of unknown etiology, characterized by chronic leukocytoclastic vasculitis. It is usually diagnosed on the basis of clinical features and histopathology. Dermoscopy is a noninvasive method for the diagnosis of various skin conditions in clinical practice. GF needs to be differentiated from various dermatoses involving the face particularly presenting with the papular morphology. Here, we present the case of a 61-year-old male patient with facial lesions, diagnosed with GF on a dermoscopic and histopathologic basis.